The Mechanical Performance evaluation of Vertical Stability Coil under Electromagnetic-structure Coupling Analyses - Han, Peng; Wang, Xianewei (Manufacturing Technology Journal, 2021)
The vertical stability coil is a set of active feedback control coil that is used to deal with the vertical instability of plasma. To improve the response performance, the coil is mounted in the vacuum vessel, which denotes the coil-body will suffer from large electromagnetic force from the plasma current and poloidal field coils. Besides the current flowing in the feeder is nearly perpendicular with magnetic field originated from toroidal coil. It implies large electromagnetic force will be generated on the feeder. In order to withstand the impact from the electromagnetic force, a series of reinforce compo-nents are designed and installed on the coil. It is necessary to verify whether or not the coil conductor and auxiliary components could successfully bear the shock of large electromagnetic force. A three-dimensional magnetic field model is built to accurately calculate the magnetic field and electromag-netic force. Corresponding to the magnetic field calculation model, a more detailed me-chanical anal-ysis model is created to launch the electromagnetic-structural coupling analysis. Based on the stress analysis results, the local structure of the coil is optimized to decrease the peak stress. The updated model is reanalyzed and stress linearization is exerted to extract the different kinds of stress on the coil components. Finally, the stress is evaluated based on ASME analytical design. The evaluation result is helpful to guide the further design optimization.
Keywords: Vertical stability; Magnetic field; electromagnetic force; Stress evaluation